Oleuropein and Verbascoside - Their Inhibition Effects on Carbonic Anhydrase and Molecular Docking Studies - Aggul, Ahmet Gokhan; Taslimi, Parham; Kuzu, Muslum; Uzun, Naim; Bilginer, Sinan; Gülçin, İlhami; Taslimi, Parham (Japan Oil Chemists Soc, 2021)
Recently, carbonic anhydrase (CA, E.C.4.2.1.1) inhibitors from natural product have paved the way for novel drug design in the treatment and prevention of some global diseases such as glaucoma, diabetes, and cancer. For this purpose, the inhibition effects of oleuropein and verbascoside from olive (Olea europaea L.) oil on human carbonic anhydrase I, and II (hCA I, and II) isoenzymes were evaluated in the current study. The inhibition effects of both natural compounds were determined by the esterase activity (in vitro). IC50 value of oleuropein and verbascoside was calculated as 1.57 and 1.73 mu M for hCA I isoenzyme, respectively. At the same manner, K-i values were determined as 1.25 +/- 0.42 and 2.00 +/- 0.42 mu M, respectively. Then, IC50 value of each compound for hCA II isoenzyme was calculated as 2.23 and 1.90 mu M, respectively. Similarly, K-i values were determined as 2.37 +/- 0.87 mu M and 1.49 +/- 0.33 mu M, respectively. Also, the inhibitory effects and potent binding mechanisms of oleuropein and verbascoside on hCA I, and II isoenzymes were realized by molecular docking studies. Consequently, both natural phenolic compounds demonstrated the potent inhibition profiles against the both isoenzymes. Therefore, we believe that these results may break new ground in the drug development for the treatment of some global disorders.
Keywords: Oleuropein; Verbascoside; Carbonic Anhydrase; Enzyme Inhibition; Molecular Docking